4.3y+8(6-y)y=2

Simple and best practice solution for 4.3y+8(6-y)y=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4.3y+8(6-y)y=2 equation:



4.3y+8(6-y)y=2
We move all terms to the left:
4.3y+8(6-y)y-(2)=0
We add all the numbers together, and all the variables
4.3y+8(-1y+6)y-2=0
We multiply parentheses
-8y^2+4.3y+48y-2=0
We add all the numbers together, and all the variables
-8y^2+52.3y-2=0
a = -8; b = 52.3; c = -2;
Δ = b2-4ac
Δ = 52.32-4·(-8)·(-2)
Δ = 2671.29
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(52.3)-\sqrt{2671.29}}{2*-8}=\frac{-52.3-\sqrt{2671.29}}{-16} $
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(52.3)+\sqrt{2671.29}}{2*-8}=\frac{-52.3+\sqrt{2671.29}}{-16} $

See similar equations:

| 7b-2/5=6-7/5 | | 3y-y=36 | | 5.1+(7+y)y=4 | | 22x=1623x=x | | 9+v-4=54 | | 9+(x-4)=54 | | x-4+9=54 | | x*2+19x-1176=0 | | 27=10p | | 2/9k=-12 | | 6(1+x)=-12 | | 4+-6-2+x=-7 | | (5x+20)+(9x+92)=180 | | 9/4*14=112/4*h | | 3x²+3=10x | | 9x+7x=-16 | | 33-2x=55-4 | | -5x-4+3=-11 | | 100x-9=317 | | 46-2i=42+7i•6 | | 100x-9=311 | | 100x-9=327 | | 10x+5=37 | | 6x-1=38 | | 1/3-x+1/4=x/3 | | 2x+9=2x+11 | | x/3-3/4=4x+9/3 | | .14x=0 | | -4x-8=6x-4 | | 6-5x/8=1-(x-5) | | 3-5x=3x-9 | | 3/5b=-21 |

Equations solver categories